The Effect of Aging Time on Biosynthesis of Zirconia Nanoparticles by Nanocellulose Templates - Ratih Resti Astari; Didit Nur Rahman; Rifki Septawendar; Bambang Sunendar Purwasasmita (Balai Besar Keramik, 2021)
In this study, the biosynthesis of ZrO2 nanomaterials was carried out using nano cellulose template from the biomass of oil palm empty fruit bunches (Elaeis guineensis). The purpose of this study was to determine the effect of nanocellulose from oil palm empty fruit bunches as a template and aging time in the formation of ZrO2 nanoparticles. The method in this research for synthesis of ZrO2 nanoparticles is the template-precursor method. The biosynthesis of ZrO2 nanoparticles calcined at 600 °C produced a metastable tetragonal phase with a nanorod-like morphology with diameter <100 nm, length <200 nm and agglomeration of nanoparticles with an average particle size of 13 nm - 17 nm.